Evaluation of modal parameters and static characteristics for composite mono leaf spring. (March 2021) - Samir Mohamed Mohamed Soliman, Ehab
The objective of this paper was to investigate and evaluate modal parameters and static characteristics for designed carbon/epoxy composite CFRP leaf spring made from carbon ﬁber-reinforced epoxy by comparing its finite element analysis FEA modal, harmonic and static results to that of conventional steel one under the same maximum full bump load. In ANSYS software, finite element modal, harmonic and static analysis for 3D models of conventional steel and designed composite mono leaf springs is carried out. FEA displacements for the steel and designed composite CFRP mono leaf springs at the maximum full bump load were 92.9 mm and 93.1 mm respectively. Compared to the steel mono leaf spring, the composite mono leaf spring has advantages; lower stresses, higher natural frequencies and higher safety in stresses of front and rear eyes. All these advantages let the composite leaf spring can be carried maximum full bump load with enough higher performance over steel one to avoid resonance and satisfy maximum stress failure criterion.